2013
DOI: 10.2903/j.efsa.2013.3468
|View full text |Cite
|
Sign up to set email alerts
|

Statement of EFSA on host plants, entry and spread pathways and risk reduction options for Xylella fastidiosa Wells et al.

Abstract: Following a request from the European Commission, EFSA was asked to provide urgent scientific and technical assistance on the plant pathogenic bacterium Xylella fastidiosa. X. fastidiosa was detected in olive trees in Lecce province in Apulia, Italy, in October 2013. This is the first outbreak of X. fastidiosa under field conditions in the European Union. EFSA reviewed the host range and vectors, the pathways for entry and spread and the risk reduction options. Known hosts include many cultivated and spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Saponari et al [5] demonstrated that olive trees with leaf scorch symptoms (i.e., branches with basal and apical pale green leaves, later expressing different degrees of scorching starting at the leaf tips, partial defoliation, and death of shoots and branches) were positive for Xylella fastidiosa Wells et al subspecies pauca, sequence type (ST) 53 (Xanthomonadales, Xanthomonadaceae) [6]. This study was the first widespread detection of this bacterium in Europe, and a quarantine around the infected area was imposed [7]. Unfortunately, quarantine was not able to limit the diffusion of the bacterium and, by the end of 2013, the affected area had grown to almost the entire Salento Peninsula.…”
Section: Introductionmentioning
confidence: 73%
“…Saponari et al [5] demonstrated that olive trees with leaf scorch symptoms (i.e., branches with basal and apical pale green leaves, later expressing different degrees of scorching starting at the leaf tips, partial defoliation, and death of shoots and branches) were positive for Xylella fastidiosa Wells et al subspecies pauca, sequence type (ST) 53 (Xanthomonadales, Xanthomonadaceae) [6]. This study was the first widespread detection of this bacterium in Europe, and a quarantine around the infected area was imposed [7]. Unfortunately, quarantine was not able to limit the diffusion of the bacterium and, by the end of 2013, the affected area had grown to almost the entire Salento Peninsula.…”
Section: Introductionmentioning
confidence: 73%
“…In October 2013, analyses conducted by Boscia's team demonstrated that the disease -named «Olive Quick Decline Syndrome» (OQDS) -was indisputably associated with the presence of X. DNA on all the diseased plants. Within a month, the Regional Council of Apulia issued an emergency plan (Regione-Puglia Dgr 2023/2013), approved by the European Food Safety Authority (Efsa 2013): since there was (and still is) no cure, the only possible options to prevent an outbreak were pruning, eradication of trees with symptoms, and use of chemical treatments against vector insects (Saponari et alii 2014).…”
Section: The Case Under Scrutinymentioning
confidence: 99%
“…Xylella fastidiosa is a polyphagous bacterium and it has been detected in 679 host species [7], but does not cause disease in most of these [8]. In 2013, it was already known that Xf (regardless of subspecies) had 132 host species belonging to 46 different families [9]. In 2016, the number of host species discovered had already risen to 329, belonging to 75 different families, and in 2018 it reached 563 species from 82 different botanical families [10].…”
Section: Introductionmentioning
confidence: 99%